Wealth Not by Any Other Name: Inland African Material Aesthetics in Expanding Commercial Times, ca. 16th-20th Centuries - Seligman, Andrea Felber (The International journal of African historical studies, 2015)
[...]a woman who wore brass wire was a prodigy; she was conspicuous and above all others. - Less than a century earlier, Abdallah's fellow Yao language speakers were considered to be some of the key middlemen in the East African ivory and slave trades. [...]many would expect that the key indicator of wealth among the Yao would be imported luxury goods or perhaps wealth in people or slaves.